Platform Approaches in the AEC Industry: Stakeholder Perspectives and Case Study - Layla Mujahed; Gang Feng; Jianghua Wang (Buildings)
The architecture, engineering, and construction (AEC) industry faces challenges related to inefficiencies and fragmentation that highlight the need for advanced construction technologies and drive interest in innovative solutions such as the platform approach to design. This study assessed platform-based building design through (1) interviews with practitioners from China, Jordan, and the UK, which helped to define the platform approach in the AEC industry and the challenges involved, and (2) a residential building design simulation conducted to evaluate the potential of the platform approach. The simulated design’s materials costs, energy efficiency, and construction time were compared with those of the traditional building design. The results of the comparison corroborate the interview findings concerning practitioners’ perspectives on platform definition, benefits, challenges, and implementation. The findings also demonstrate the potential of the platform approach to enhance productivity and scalability through modularization, kit-of-parts configuration, and standardization. This research bridges the gap between theory and practice by supporting shareholder perspectives on building design and construction with the results of a simulated platform approach to a real-world design project. This research addresses the urgent need to better understand and test the platform approach to achieve material, energy, and construction time savings through collaborative and practice-informed design.